New perspectives in treating high-risk cardiac patients. Rosuvastain and it’s perspectives for clinical practice use - M. G. Bubnova (Кардиоваскулярная терапия и профилактика)
The review summarizes modern principles of lipid-lowering therapy aimed at cardiovascular event risk reduction. The author describes main patient groups in need for early, aggressive lipid-lowering therapy – predominantly, statin therapy. New statin treatment tactics is presented, based on the latest results of recent large-scale clinical trials. The article also contains the results of clinical trials on a new generation statin, rosuvastatin, its lipid-lowering and anti-atherosclerotic effects, its pharmacological features and clinical use perspectives.